Predation rate by wolves on the Porcupine caribou herd - Hayes, Robert D.; Russell, Donald E. (Rangifer, 2000)
Large migratory catibou {Rangifer tarandus) herds in the Arctic tend to be cyclic, and population trends are mainly driven by changes in forage or weather events, not by predation. We estimated daily kill rate by wolves on adult caribou in winter, then constructed a time and space dependent model to estimate annual wolf (Canis lupus) predation rate (P annual) on adult Porcupine caribou. Our model adjusts predation seasonally depending on caribou distribution: Pannual = SIGMAdaily* W *Ap(2)*Dp. In our model we assumed that wolves killed adult caribou at a constant rate (Kdaily, 0.08 caribou wolf1 day1) based on our studies and elsewhere; that wolf density (W) doubled to 6 wolves 1000 km2-1 on all seasonal ranges; and that the average area occupied by the Porcupine caribou herd (PCH) in eight seasonal life cycle periods (Dp ) was two times gteater than the area described by the outer boundaries of telemetry data (Ap /1000 km2). Results from our model projected that wolves kill about 7600 adult caribou each year, regardless of herd size. The model estimated that wolves removed 5.8 to 7.4% of adult caribou as the herd declined in the 1990s. Our predation rate model supports the hypothesis of Bergerud that spacing away by caribou is an effective anti-predatory strategy that greatly reduces wolf predation on adult caribou in the spring and summer.